2013
DOI: 10.1175/jamc-d-12-0109.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Different Land Use and Land Cover Patterns on Mesoscale Meteorological Simulations in the Taiwan Area

Abstract: The U.S. Geological Survey (USGS) land use (LU) data employed in the Weather Research and Forecasting (WRF) model classify most LU types in Taiwan as mixtures of irrigated cropland and forest, which is not an accurate representation of current conditions. The WRF model released after version 3.1 provides an alternative LU dataset retrieved from 2001 Moderate Resolution Imaging Spectroradiometer (MODIS) satellite products. The MODIS data correctly identify most LU-type distributions, except that they represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 15 publications
3
56
0
1
Order By: Relevance
“…In the case of Austria, Schicker et al [12] found many more urban grid cells in their updated land-use database compared with the default USGS data, resulting in higher and better-simulated temperature when using their updated input. Cheng et al [13] also indicated that most regions of Taiwan were not classified as urban areas in the USGS data, contrary to the actual situation, thereby under-predicting temperature in urban areas. The present findings are consistent with these examples.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Austria, Schicker et al [12] found many more urban grid cells in their updated land-use database compared with the default USGS data, resulting in higher and better-simulated temperature when using their updated input. Cheng et al [13] also indicated that most regions of Taiwan were not classified as urban areas in the USGS data, contrary to the actual situation, thereby under-predicting temperature in urban areas. The present findings are consistent with these examples.…”
Section: Discussionmentioning
confidence: 99%
“…Land use and land cover change associated with urbanization considerable impact on climate [1]. One of the results is a consistent rise in temperature in the urban atmosphere because of the land-use changes and accompanying effects on physical processes governing energy, momentum and matter exchange between land surface and the atmosphere [2,3]. Guangzhou, the capital and largest city of Guangdong province and the 3rd largest Chinese city, is undergoing a rapid and widespread urbanization and a deterioration of urban environments caused by urban heat islands.…”
Section: Introductionmentioning
confidence: 93%
“…Such tremendous urban expansion accompanied with increasing built-up areas and intensifying human activities causes remarkable modifications of the underlying surface properties, thereby significantly enhancing the UHI effect [17]. Previous studies show that the UHI effect noticeably contributes to regional warming in Guangzhou area [21].…”
Section: Model Configurationmentioning
confidence: 99%
“…The coupled WRF/UCM modeling system has been applied to many regions, such as Houston, USA [6], Nanjing, China [7], and New York, USA [8], and its performance has been evaluated against observations. expansion accompanied with increasing built-up areas and intensifying human activities causes remarkable modifications of the underlying surface properties, thereby significantly enhancing the UHI effect [17]. Previous studies show that the UHI effect noticeably contributes to regional warming in Guangzhou area [21].…”
Section: Introductionmentioning
confidence: 99%